Blockchain-based decentralized security using Crypto-Proof of Stake for securing sensitive personal health care records. (November 2022) - K M, Deepika; H A, Sanjay; M K, Mohan Murthy
Highlights: The blockchain is tremendous technology for securing data transmission over a decentralized cloud environment. The lattice construction phase develops the blockchain security on the distributed decentralized network initially to process the security. The Random shuffle block Padding is intended to rehashing the block to score with padding bits to block level encryption. The Delegate proof of stack provides higher security to protect the sensitive terms by accessing PHR records transactions to improve the integrity proofing to the admittance of the key to deliver the data. This proves a higher security protocol and authentication principle than any other method as well as security proofing. Abstract: The blockchain is tremendous technology for securing data transmission over a decentralized cloud environment. A PHR can offer easy data exchange and storage. However, unauthorised individuals may steal sensitive users' data from cloud devices, leading to significant privacy leakage risks. The main problem is that the non-authentication policy leads to key leakages due to unauthorised entries through intruders. To resolve this problem, we propose Blockchain-Based Decentralized Security (BCDS) using Crypto-Proof of Stake (CPoS) for securing sensitive Personal health care records. First, to process the security, the lattice construction phase is used based on blockchain decentralized. The Random shuffle block padding is intended to rehash the block to score with padding bits to block-level encryption. Then the sensitive terms are marginalized by threshold labels being highly encrypted by Optimized Starvation Point Link Encryption (OSPLE) to protect the data. By integrating Master Node Key Aggregation Policy (MNKAP) to verify the contact proof of staking authentication to the peer end to authenticate the security. The Delegate proof of stack provides higher security to protect the sensitive terms by accessing PHR records transactions to improve the integrity proofing to the admittance of the key to deliver the data. The key signature verification then validates the key for authentication to decrypt the protected data. This proves a higher security protocol and authentication principle than any other method as well as security proofing.